Exposure-Based Cash-Flow-at-Risk for Value-Creating Risk Management under Macroeconomic Uncertainty - Niclas Andrén; Håkan Jankensgård; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2010)
A strategically minded CFO will realize that strategic corporate risk management is about finding the right balance between risk prevention and proactive value generation. Efficient risk and performance management requires adequate assessment of risk and risk exposures on the one hand and performance on the other. Properly designed, a risk measure should provide information on to what extend the firm's performance is at risk, what is causing that risk, the relative importance of non-value-adding and value-adding risk, and the possibilities to use risk management to reduce total risk. In this chapter, we present an approach exposure-based cash-flow-at-risk to calculating a firm's downside risk conditional on the firm's exposure to non-value-adding macroeconomic and market risk and to analyzing corporate performance adjusted for the impact of non-value-adding risk.
Keywords: E32; G32; G33; G34; M16; M21; 330; Cash-flow-at risk; Value at risk; Risk management; Value creation; Total risk; Cash Flow; Risikomanagement; Risikomaß; Unternehmenserfolg; Performance-Management